PENGARUH PELATIHAN KERJA, KEMAMPUAN KERJA DAN PROMOSI JABATAN TERHADAP PRESTASI KERJA KARYAWAN NON MEDIS PADA RUMAH SAKIT JIWA TAMPAN PEKANBARU - Siti Nurhaliza; Okta Karneli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
In the era of globalization that is increasingly advanced and developing, a company or organization must be able to develop human resources, including human resources in hospitals. The object of this research is the Tampan Pekanbaru Mental Hospital, abbreviated as RSJ Tampan. This study aims to determine how much influence job training, job skills, and job promotion have on the work performance of non-medical employees at the Tampan Mental Hospital Pekanbaru. The research method uses quantitative data collection through questionnaires and interviews. The focus of sampling in this study were 83 non-medical employees of the PNS (Civil Service) section at the Tampan Hospital with the Purposive Sampling technique method. The data analysis technique used is simple linear regression analysis and multiple linear regression analysis using SPSS 25. Based on the results of the research hypothesis test, it shows that there is a partially significant effect between job training on job performance, work ability on job performance, and job promotion on job performance. non-medical employees of the Handsome Hospital, then the simultaneous effect of job training, job skills, and job promotions on the work performance of non-medical employees at the Tampan Hospital Pekanbaru. Keywords: Job Training, Job Ability, Job Promotion, and Job Performance.